The effect of arginine on oral biofilm communities. (2nd December 2013) - Nascimento, M.M.; Browngardt, C.; Xiaohui, X.; Klepac‐Ceraj, V.; Paster, B.J.; Burne, R.A.
Summary Alkali production by oral bacteria via the arginine deiminase system (ADS) increases the pH of oral biofilms and reduces the risk for development of carious lesions. This study tested the hypothesis that increased availability of arginine in the oral environment through an exogenous source enhances the ADS activity levels in saliva and dental plaque. Saliva and supra‐gingival plaque samples were collected from 19 caries‐free (CF) individuals (DMFT = 0) and 19 caries‐active (CA) individuals (DMFT ≥ 2) before and after treatment, which comprised the use of a fluoride‐free toothpaste containing 1.5% arginine, or a regular fluoride‐containing toothpaste twice daily for 4 weeks. ADS activity was measured by quantification of ammonia produced from arginine by oral samples at baseline, after washout period, 4 weeks of treatment, and 2 weeks post‐treatment. Higher ADS activity levels were observed in plaque samples from CF compared to those of CA individuals (P = 0.048) at baseline. The use of the arginine toothpaste significantly increased ADS activity in plaque of CA individuals (P = 0.026). The plaque microbial profiles of CA treated with the arginine toothpaste showed a shift in bacterial composition to a healthier community, more similar to that of CF individuals. Thus, an anti‐caries effect may be expected from arginine‐containing formulations due in large part to the enhancement of ADS activity levels and potential favorable modification to the composition of the oral microbiome.